From the carrier of active substance to drug delivery systems - Jadach, Barbara (Journal of Medical Science, 2017)
Development and innovation all the time are in interests of pharmaceutical science and evaluation of different dosage forms. They are concerned with the aim of compliance of patients. All the time different research groups try to develop and improve form of drugs to receive better bioavailability or strict control of dose, place and time of action of active substances. This is possible by using different excipients; biodegradable, biocompatible polymers that work like a carriers; developing simple drug delivery systems, which in time became more and more complicated; nanotechnology that control size, shape and multi-functionality of particulate drug delivery systems. This review shows the main points in the evaluation of pharmaceutical researches from simple carriers of active substances to drug delivery systems.
Keywords: carrier; drug delivery system; sustained release; zero-order kinetic; nanoparticle